Understanding the Relationship between Organizational Networking and Network Capability - Hutu, Raul Alexandru (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Organizational networking refers to firms‘ behaviours as activities, routines, practices which enable an organization to make sense of and capitalize on their networks of direct and indirect business relationships. The relationships are more important today when the business environment is more competitive. The firms can develop their organizational networking strategies by developing their network capability which refers to its ability to build, handle and exploit relationships. These capabilities are included in a complex configuration with other capabilities and competencies. The aim of this paper is to explore how network capabilities are structured and we tried to understand how they could be improved in order to obtain higher performance. Achieving a good network position that allows firms to make use of business opportunities is a main strategic aim of firms.